ECONOMIC LOSS OF SOCIETY FROM IMPRISONMENT - จารุจิตติพันธ์, พิศมัย; การเกษตร, จรัสสา (RMUTT Global Business and Economics Review, 2019)
This research aimed to study the social economic status, Population’s characteristics and evaluate economic loss of society from imprisonment of the 4,674 prisoners in Central Woman Correctional Institution and research by study from documents to analyze and synthesize from primary and secondary data. The research were found that during the past 19 years (1999 – 2018) the most of prisoners in the Central Women Correctional Institution were 30-39 years old, graduated the vocational education level and against the Narcotics Act case. The total of the economic loss of society from imprisonment in the Central Female Correctional Institution were 3,891,921,550.76 Bath. Consisting of the value of economic loss in terms of female prisoners 3,519,335,407.62 baht, the economic loss of family members of female prisoners 165,801,600 baht and the value of economic loss of the state 206,784,543.14 baht. The prisoner who got the most economic loss of society was a prisoner of the Narcotics Act for 19 years imprisonment. The prisoner with the lowest economic loss value was a prisoner of the Narcotics Act imprisoned for 1 year. The value ratio of economic loss in responsibility of female prisoners and their family by the value of economic loss in responsibility of governance was 95.15 : 4.85 .